Professional management consulting : a guide for new and emerging consultants - Blackman, Alan J. (Routledge, 2024)
"At a time when consulting has increasingly come under scrutiny by governments and communities, Professional Management Consulting: A Guide for New and Emerging Consultants redefines "management consulting" and reinforces what it means to be a professional. With a focus on the importance of ethical practice and continuous personal development for building reputation, this easy-to-read book sets a new benchmark for aspiring consultants. Based on sound research and supported by the author's background in leadership, management consulting practice, research, business strategy, and academia over several decades, Blackman brings together a range of tried and tested theoretical models commonly used by successful consultants. Drawing on his own experiences as a director of the industry's peak body, the Institute of Management Consulting Institutes, he provides a clear explanation on what a management consultant is and how and why clients use consultants to help them solve complex problems and manage change. With an emphasis on the importance of building and recognising relationships as a basis for problem-solving and implementing change, this book is an essential contribution to the profession worldwide. A vital resource for new and emerging professional consultants. It is suitable as an introductory text for business/commerce and engineering undergraduate students and a secondary reading for graduate students in engineering and management"-- Provided by publisher.
Keywords: Business consultants.; Consultants.; Organization.; elektronické knihy; electronic books